Pseudoelastic fatigue of NiTi wires: frequency and size effects on damping capacity - Soul, Hugo Ramon (2010)
The damping properties associated with hysteretic behavior of the pseudoelastic stress–strain (σ–ε) curves of NiTi shape memory alloy (SMA) wires were studied. Damping was  characterized for wires of 2.46 and 0.5 mm diameter using samples of 120 mm in length. The effect of the frequency and size of the wire on the σ–ε curves were studied in the 3 × 10 − 5–3 Hz range, with 8% maximal strain. Damping associated parameters, such as hysteresis width, dissipated energy and specific damping capacity (SDC), defined as the ratio between the hysteretic energy and the maximum strain work over a complete pseudoelastic cycle, show maximum values at a specific frequency for each size diameter. These findings were explained in terms of the temperature effects associated to the heat of transformation. Results show that NiTi wire of 0.5 mm diameter has the highest SDC when cycling around 0.1 Hz while wire of 2.46 mm diameter has the highest SDC at 0.01 Hz. At 1 Hz, the SDC for 0.5 mm diameter wire is around twice that of 2.46 mm diameter wire.